1996
DOI: 10.1007/bf00057594
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal evolution in salmonids: a comparison of Atlantic salmon, brown trout, and rainbow trout R-band chromosomes

Abstract: Replication banding technique was applied to the chromosomes of Salmo salar, Salmo trutta, and Oncorhynchus mykiss. The in vitro technique has proved more advantageous than the in vivo technique due to a higher number of bands obtained. The comparison of these replication banding patterns has revealed that some chromosomes of Salmo trutta karyotype appeared associated with Salmo salar and Oncorhynchus mykiss karyotypes by single chromosomal rearrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Metaphase chromosomes were prepared for FISH analysis from stimulated peripheral blood lymphocytes according to Fujiwara et al [21]. This method provided greater reproducibility, higher mitotic index (MI), shorter culture time and nonlethality compared to other methods used for rainbow trout [22]. FISH was performed as described [23] with some modifications.…”
mentioning
confidence: 99%
“…Metaphase chromosomes were prepared for FISH analysis from stimulated peripheral blood lymphocytes according to Fujiwara et al [21]. This method provided greater reproducibility, higher mitotic index (MI), shorter culture time and nonlethality compared to other methods used for rainbow trout [22]. FISH was performed as described [23] with some modifications.…”
mentioning
confidence: 99%
“…The four populations of C. humboldtianum analyzed in this study showed a diploid number (2n = 48), which concurs with the most frequent diploid number found in Atheriniformes (Atherinopsidae, in Labidesthes, Membras and Menidia, Jeffrey & Fitzsimons, 1987;Warkentine et al, 1987;Odontesthes, Sola et al, 1988;Basilichthys, Gajardo, 1992;and Atherinella, Da Silva Cortinhas et al, 2003;Sczepanski et al, 2007). It is also considered to be the ancestral number for several freshwater teleost fish (i.e., salmonids, Amaro et al, 1996;cichlids, Thompson, 1979;Arias-Rodríguez et al, 2006) and even marine fishes (Galetti et al, 2000). Overall, within the family, the diploid number 2n = 48 is a conserved characteristic, except for C. patzcuaro (2n = 44) (Uribe-Alcocer et al, 2002;Uribe-Alcocer & Díaz-Jaimes, 2003).…”
Section: Discussionmentioning
confidence: 99%